Criticism and Defense: The Buddhist View of Chinese Jesuit Li Wenyu in the Late Qing Dynasty - CHANG, Kai (Journal of Research for Christianity in China (JRCC), 2025)
In the late Qing Dynasty, there were frequent missionary cases. Chinese Jesuit Li Wenyu and other Catholics actively wrote Sino-Chiristian Theology works to explain and protect Catholicism, which involved Buddhism. Although Buddhism was not the main debate of Catholicism in this period, Li Wenyu worships the Catholic, and his apologetics thought was reflected in criticizing Buddhism and Taoism. Based on the Catholic theology standard, he criticized the buddhist theory of reincarnation from the perspective of Confucian ethics, western knowledge and the historical reality of Buddhism. In addition, Li Wenyu also drew lessons from Matteo Ricci's The True Meaning of the Lord of Heaven in his criticism of Buddhism. The analysis of Li Wenyu's Buddhist view will help us to clarify the relationship between Catholicism and Buddhism in the late Qing Dynasty, and it also has some reference significance for the study of the dialogue between Catholicism and Buddhism in the late Qing Dynasty.